1D morphodynamic modelling using a simplified grain size description. Issue 2 (4th March 2018) - Camenen, Benoît; Béraud, Claire; Le Coz, Jérôme; Paquier, André
ABSTRACT: This paper introduces an 1D numerical code RubarBE for hydraulic and mobile-bed simulations. The code's ability to reproduce the downstream fining of a gravel–sand mixture in response to bed aggradation is tested against laboratory experiments. Unlike in most numerical models, grain size distribution in each sediment layer is not represented using a multi-class model, but using the median diameter and a sorting coefficient σ . The comparison of numerical results with experimental data shows that the adaptation length, classically used for non-equilibrium sediment transport, is an essential parameter of the model to accurately reproduce the evolution of the deposit front. Empirical laws for adjustments of and σ are proposed to reproduce sediment sorting through two grain-size related adaptation lengths (, ). They are scaled by the length of the reach in morphological equilibrium, which is a useful result for field applications.